Half the sky turning oppression into opportunity for women worldwide - Kristof, Nicholas D. 1959- (Alfred A. Knopf, 2009)
Two Pulitzer Prize winners issue a call to arms against our era's most pervasive human rights violation: the oppression of women in the developing world. They show that a little help can transform the lives of women and girls abroad and that the key to economic progress lies in unleashing women's potential.